Pemanfaatan Aplikasi Customer Relation Management pada koperasi - Samuel Manurung; Mufria J. Purba (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
Cooperatives are usually referred to as a means to help people from low economic circles up to economic conditions upwards. With the existence of a unit for savings and loans can help the community in the district of Kabanjahe open a business in improving the economy of the people in Kabanjahe. Payment of invoices by customers and events to be carried out by cooperatives never arrive due to a lack of information received by customers. Therefore we need a system that is very helpful in the process of supporting events in the cooperative. The CRM (Customer Relationship Management) application can assist in the notification process and simplify the cooperative payment transaction process. This research can facilitate the cooperatives and cooperative members in conducting transactions and is very helpful also to customers in the notification process of cooperative activities and customer bills and notifications are given 3 days before the activities or events from CU.